Pengaruh Metode Inqury Discoveri Learning Terhadap Hasil Belajar PKn Siswa Kelas IV SDN 139 Kecamatan Duampanua Kabupaten Pinrang - Jumiati Nur; Andi Sugiati (JED (Jurnal Etika Demokrasi), 2018)
This research is research that want to know difference of result of student learning when given treatment or treatment with not given treatment or treatment to fourth grade student of SDN 139 District of Duampanua Regency of Pinrang, subject of this research is fourth grader student of subject year 2016 subject 32 student. Technical data through pretest and posttest data and observation and analyzed descriptively and hypothesis test. The results showed that the learning of Civics through learning method of Inquiry Discoveri Learning can improve student's learning result of Civitas compared to tampa with method average 61,4 after giving average score 75,4. English learning activities using learning methods. Discover learning Improved learning by seeing students begin to be active and pay attention to taught material, do the job well and correctly, enthusiastic to ask questions to the teacher and answer questions given. Students who just simply imitate at the time doing the task began to appear curiosity how to complete the task given.Keywords: Inquiry Discoveri Learning, Learning Outcomes, Civics